1996
DOI: 10.1183/09031936.96.09020202
|View full text |Cite
|
Sign up to set email alerts
|

Differential activity of nitric oxide synthase in human nasal mucosa and polyps

Abstract: Nitric oxide (NO) plays an important regulatory role in airway function and seems to be implicated in the pathophysiology of several airway diseases. To better understand the involvement of NO in the upper airways, we examined the presence of nitric oxide synthase (NOS) activity in human nasal mucosa and nasal polyp tissues. Nasal mucosa was obtained from seven patients undergoing septoplasty, and nasal polyps came from nine patients following polypectomy. NOS activity was quantified in tissue homogenates usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
43
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 30 publications
5
43
1
Order By: Relevance
“…NO, generated via iNOS, which is induced in inflammatory cells and epithelium of the upper respiratory tract, is an important mediator in modulating the inflammatory and immunological response [18,39]. Involvement of NO was shown for rhinitis based on house dust mite allergy [13], seasonal rhinitis [11], chronic rhinitis [15] and nasal polyps [14]. NO levels are high in exhaled air, which was shown to be originating mainly from the nasal and paranasal airways [34, 40±42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NO, generated via iNOS, which is induced in inflammatory cells and epithelium of the upper respiratory tract, is an important mediator in modulating the inflammatory and immunological response [18,39]. Involvement of NO was shown for rhinitis based on house dust mite allergy [13], seasonal rhinitis [11], chronic rhinitis [15] and nasal polyps [14]. NO levels are high in exhaled air, which was shown to be originating mainly from the nasal and paranasal airways [34, 40±42].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that considerable levels of NO metabolites are present in nasal lavage fluid of patients with house dust mite allergy [12] and that nasal polyps contain higher levels of NOS than normal nasal mucosa [13]. In addition, the exact localization of NOS in nasal mucosa has been identified [14,15].…”
mentioning
confidence: 99%
“…Firstly, the normal, noninflamed nasal mucosa can itself express NOS [18] . Secondly, it has recently been shown that the epithelium of the polyps, which originate from the sinus, express the inducible type III NOS [19]. Consequently, the polyps can also generate NO and may themselves contribute to NO production.…”
Section: Discussionmentioning
confidence: 99%
“…For the NF-kB deoxyribonucleic acid (DNA)-binding activity assay, pieces of tissue were immediately frozen in liquid nitrogen and stored at -808C. For the immunohistochemical techniques, the tissues were cut into several pieces of~5-mm thick and fixed in periodate-lysine-paraformaldehyde, frozen in Tissue-Tek1 ornithine carbamoyltransferase (OCT) medium (Miles Laboratories, Elkhart, IN, USA) and processed as previously described [13]. For epithelial cell culture, intact tissues were placed in Dulbecco's modified Eagle's medium (DMEM)/Ham's F12 medium 1:1 (Life Technologies, Merelbeke, Belgium) and immediately transported on ice to the laboratory for processing.…”
Section: Tissue Processingmentioning
confidence: 99%
“…Increasing evidence, based upon higher than normal levels of nitric oxide in the exhaled air of asthmatic patients [10,11] and prominent immunostaining for iNOS in asthmatic airway epithelium [12], suggests that the iNOS isoform may play a role in acute and chronic inflammatory airway diseases. In the upper airways, increased iNOS activity [13] and expression [14] have been shown in chronically inflamed nasal polyp tissues. Despite the reported iNOS upregulation under inflammatory conditions, exciting new findings have demonstrated that iNOS is continuously expressed in normal airway epithelium [15], implying a homeostatic role for this isoform not previously considered.…”
mentioning
confidence: 99%